PENERAPAN MODEL PEMBELAJARAN KONSTRUKTIVISME PADA MATERI CIRI-CIRI MAHLUK HIDUP DI KELAS III A SD NEGERI KEPUTRAN - Sujarwanto, Sujarwanto (Mimbar Sekolah Dasar, 2016)
Formulation of the problem this research is how the learning process, how much improving student learning outcomes on the material characteristics of living things, and change the behavior of learners with learning model constructivism in third-grade students of Keputran 06 Elementary School. A Classroom Action Research was conducted in two cycles, behavioral changes towards better aspects of attention, student response, responsibility, how students respond, and make a note of student activity during the learning process. The average results of the first cycle of learning 83,07 with minimum completeness criteria, students who achieve 77%, while on the second cycle, students get an average of 90.76 with students who achieve 100% minimum completeness criteria.Keywords: learning model constructivism, two dimensions media, three dimensions media.